P925 Deep functional assessment of the colonic mucosa-associated microbiota in Crohn's disease and health identifies pro- and anti- inflammatory secretomes and associated bacterial consortia. The ENIGMA study. (30th January 2023) - Teh, J J; Kang, S; Zhang, J; Hu, J; Hamilton, A L; Wilson-O'Brien, A; Trakman, G L; Lin, W; Ching, J; Sung, J J Y; Yu, J; Ng, S C; et al.
Abstract: Background: Gut microbial dysbiosis and dysregulated host immune responses are key factors implicated in Crohn's disease pathogenesis. However, the nexus between the mucosa-associated microbiota (MAM) and epithelial cell immune response(s) remains poorly understood. Here, we used in vitro cultures of LS174T human epithelial cells to examine the inflammatory tenor of the secretomes from colonic MAM recovered from healthy and Crohn's disease subjects in Hong Kong (where Crohn's disease incidence is low but increasing) and Australia (globally high incidence). Methods: Biopsies from healthy (21 HKG, 20 AUS) and Crohn's disease (30 HKG, 29 AUS) subjects were collected from the right colon and the MAM propagated from tissue using a habitat simulating medium. After 24h of growth, cultures were centrifuged, and the supernatant (secretome) fraction filter sterilised. For the immune assays, the LS174T cell line was transfected with recombinant lentivirus to provide an NF-κB: luc (luciferase) reporter gene fusion (Cellomics Technology, MD, USA) and aliquots used to inoculate 96-well microtiter plates and cultured for 24 h under standard conditions. Cultures were then challenged for 4 hours with 0.1 vol of a MAM secretome. Luc-bioluminescence was measured as a marker of NF-κB transcriptional activity from the individual wells and normalised to the reporter gene response from cells challenged with sterile, uninoculated bacterial medium. Results: Across the 100 MAM secretomes tested, the median score for NF-ĸB activation was 104.4% relative to the medium control, suggesting most of the secretomes possessed a net neutral effect, with the 1st and 4th quartiles deemed stimulatory (>126% baseline activity) and suppressive (<92% baseline activity), respectively. There was no significant relationship found between a secretome's inflammatory score and its corresponding α-diversity metric, nor was there any distinct clustering of the secretomes according to country of origin and/or case-control groups. However, the relative abundances of Roseburia spp. and Clostridium innocuum were significantly enriched in those consortia producing immunostimulatory secretomes. In contrast, the relative abundances of Erysipelatoclostridium ramosum, Ruminococcus gnavus, Parabacteroides distasonis, Blautia sp. CAG257 and Bacteroides xylanisolvens were enriched, and that of Coprococcus comes depleted, in those microbial consortia producing immunosuppressive secretomes. Conclusion: Specific bacterial taxa drive the functional signature of the colonic MAM secretome in an immunostimulatory or suppressive direction. The ENIGMA study is supported by a grant from the Leona M. and Harry B. Helmsley Charitable Trust